Walk with me - Danis, Naomi; Rogers, Jacqueline (New York : Cartwheel Books, 1995)
A toddler and her mother enjoy all the sights and sensations on a walk to the park.
"A Lucas Evans book"--Verso t.p.
Keywords: Walking -- Fiction; Mother and child -- Fiction; Toddlers -- Fiction